A randomised, controlled, double blind, non‐inferiority trial of ultrasound‐guided fascia iliaca block vs. spinal morphine for analgesia after primary hip arthroplasty. (7th October 2016) - Kearns, R.; Macfarlane, A.; Grant, A.; Puxty, K.; Harrison, P.; Shaw, M.; Anderson, K.; Kinsella, J.
Summary: We performed a single centre, double blind, randomised, controlled, non‐inferiority study comparing ultrasound‐guided fascia iliaca block with spinal morphine for the primary outcome of 24‐h postoperative morphine consumption in patients undergoing primary total hip arthroplasty under spinal anaesthesia with levobupivacaine. One hundred and eight patients were randomly allocated to receive either ultrasound‐guided fascia iliaca block with 2 mg.kg −1 levobupivacaine (fascia iliaca group) or spinal morphine 100 μg plus a sham ultrasound‐guided fascia iliaca block using saline (spinal morphine group). The pre‐defined non‐inferiority margin was a median difference between the groups of 10 mg in cumulative intravenous morphine use in the first 24 h postoperatively. Patients in the fascia iliaca group received 25 mg more intravenous morphine than patients in the spinal morphine group (95% CI 9.0–30.5 mg, p < 0.001). Ultrasound‐guided fascia iliaca block was significantly worse than spinal morphine in the provision of analgesia in the first 24 h after total hip arthroplasty. No increase in side‐effects was noted in the spinal morphine group but the study was not powered to investigate all secondary outcomes.